Les lieux de la culture: une théorie postcoloniale - Bhabha, Homi K.; Bouillot, Françoise (Éditions Payot & Rivages, 2019)
Sommaire"Salué aussi bien par Edward Said que par Toni Morrison ou J.M. Coetzee, Homi K. Bhabha est l un des théoriciens les plus importants et les plus influents du postcolonialisme. S'appuyant sur la littérature, la philosophie, la psychanalyse et l'histoire, il invite notamment à repenser les questions très actuelles d'identité et d'appartenance nationales ; à dépasser, grâce au concept très fécond d'hybridité culturelle, la vision d'un monde dominé par l'opposition entre soi et l'autre ; à saisir comment, par le biais de l'imitation et de l'ambivalence, les colonisés introduisent chez leurs colonisateurs un sentiment d'angoisse qui les affaiblit considérablement ; ou encore, plus largement, à comprendre les liens qui existent entre colonialisme et globalisation." – Résumé de l'éditeur.
Keywords: approches et analyses; arts; com5170; cours; discipline; har4600; histoire; histoire et politique; identités; philosophie; postcolonialisme; premier cycle; psychanalyse; sciences; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études littéraires

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social